Comparison of EMG signals recorded by surface electrodes on endotracheal tube and thyroid cartilage during monitored thyroidectomy. Issue 10 (22nd July 2017) - Chiang, Feng‐Yu; Lu, I‐Cheng; Chang, Pi‐Ying; Dionigi, Gianlorenzo; Randolph, Gregory W.; Sun, Hui; Lee, Kang‐Dae; Tae, Kyung; Ji, Yong Bae; Kim, Sung Won; Lee, Hyoung Shin; Wu, Che‐Wei
Abstract: A variety of electromyography (EMG) recording methods were reported during intraoperative neural monitoring (IONM) of recurrent laryngeal nerve (RLN) in thyroid surgery. This study compared two surface recording methods that were obtained by electrodes on endotracheal tube (ET) and thyroid cartilage (TC). This study analyzed 205 RLNs at risk in 110 patients undergoing monitored thyroidectomy. Each patient was intubated with an EMG ET during general anesthesia. A pair of single needle electrode was inserted obliquely into the TC lamina on each side. Standard IONM procedure was routinely followed, and EMG signals recorded by the ET and TC electrodes at each step were compared. In all nerves, evoked laryngeal EMG signals were reliably recorded by the ET and TC electrodes, and showed the same typical waveform and latency. The EMG signals recorded by the TC electrodes showed significantly higher amplitudes and stability compared to those by the ET electrodes. Both recording methods accurately detected 7 partial loss of signal (LOS) and 2 complete LOS events caused by traction stress, but only the ET electrodes falsely detected 3 LOS events caused by ET displacement during surgical manipulation. Two patients with true complete LOS experienced temporary RLN palsy postoperatively. Neither permanent RLN palsy, nor complications from ET or TC electrodes were encountered in this study. Both electrodes are effective and reliable for recording laryngeal EMG signals during monitored thyroidectomy. Compared to ET electrodes, TC electrodes obtain higher and more stable EMG signals as well as fewer false EMG results during IONM.